Syntheses and Crystal Structures of Two Cadmium Methanetetrabenzoates Featured by Open Framework and Infinite Layers - Harms, Sven; Köferstein, Roberto; Görls, Helmar; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2019)
Colorless single crystals of Cd2[μ8‐MTB]·3H2O·DMF (1) were prepared in DMF/H2O solution [1: space group C2/c (no. 15) with a = 1821.30(6), b = 2175.08(6), c = 1269.87(4) pm, β = 129.684(1)°]. The connection between the methane‐p‐benzoate tetraanions (MTB4–) and the Cd2+ cations leads to a three‐dimensional framework with channels extending along [110] and [110] with openings of 670 pm × 360 pm. The channel‐like voids accommodate water molecules and N,N‐dimethylformamide (DMF) molecules not bound to Cd2+. Colorless single crystals of [Cd4(2,2′‐bipy)4(μ7‐MTB)2]·7DMF (2) were prepared in DMF in the presence of 2,2′‐bipyridine [2: space group P1 (no. 2) with a = 1224.84(4), b = 1418.85(5), c = 2033.49(4) pm, α = 85.831(2)°, β = 88.351(2)°, γ = 68.261(1)°]. The coordination of MTB4– to Cd2+ results in infinite layers parallel to (001). The layers, not connected by any hydrogen bonds, contain small openings of about 320 pm × 340 pm.